Pengembangan Makanan Khas Untuk Pemberdayaan Nutripreneurship Siswa SMA Dominikus Wonosari Gunungkidul - Lubijarsih, Maria Amrijati; Purnawijayanti, Hiasinta A.; Pujiastuti, Veronica Ima (LPPM UNINUS, 2023)
The potential of Gunungkidul district as a tourist destination is growing and the demands for entrepreneurship are increasing at this time. It encourages Dominikus Wonosari Gunungkidul High School as a partner, to launch Culinary and Entrepreneurship program. Community Service activity was carried out in order to support the program. The activity aimed to provide education, training, and grow the spirit of nutripreneurship for Dominican High School students. In addition, the activity aimed to produce graduates who are ready to work and experienced in running entrepreneurship for Dominican High School students or even when they cannot continue their education. The nutripreneurship empowerment of students was carried out by providing education and training. The education provided were include material on the concept of entrepreneurship, food product development, processing technology, packaging technology, hygiene and sanitation, as well as food safety and quality. The training provided was the practice of processing food products based on mocav flour which is a typical commodity of Gunungkidul district. Mocav flour will be processed into snack products that support Gunung Kidul district as a tourist destination. The traditional food products are pie, cookies, cake and snack food products, specifically milk pie, othello cookies, fruits, and chocochips, cake brownies and telur gabus snacks. The Empowerment of Nutripreneurship to the partners can be seen in the increasing of knowledge, skills, motivation and commitment to run Nutripreneurship. This were indicated by the results of pre- and post-test assessments, product quality from practice results, evaluation of the implementation of activities, and the implementation of follow-up programs independently by partners. The follow-up program that was carried out independently included stage 3 food processing training activities, to further strengthen the mastery of food products followed by the production and marketing process of training products in the Culinary Exhibition Program event organized by Dominikus Wonosari Gunungkidul High School